The role of endocannabinoids in Alzheimer's disease - Maroof, Nazia (2013)
The endocannabinoid system (ECS) comprises the endocannabinoids (ECs), including anandamide (AEA) and 2-arachidonoyl glycerol (2AG), which interact with the G protein-coupled type-1 and type-2 cannabinoid receptors(CB1 and CB2 respectively). The ECS is thought to have a role in a number of central processes including neuroinflammation, neurogenesis, neuroprotection, learning and memory. Due to its influence on a diverse number of processes, it has been suggested that modifying the ECS may be therapeutically beneficial in Alzheimer's disease (AD). AD is an age-related neurodegenerative disorder characterised by the presence of extracellular amyloid beta (Ab) plaques and intracellular neurofibrillary tangles (NFTs) resulting in impairments in learning in memory. The aim of this thesis was to determine the status of the brain ECS in the APPswe/PS18E9 mouse model of AD and wild type littermates at 4, 6 and 8 months of age and the performance of these animals in a behavioural test battery. The results of this study indicated that APPswe/PS18E9 animals were hyperactive compared to their wildtype counterparts at all ages and that they also displayed deficits in behavioural flexibility. EC levels increased with age in both wild type and APPswe/PS18E9 mice. Cannabinoid receptor coupling was increased in the frontal cortex and striatum of APPswe/PS18E9 mice relative to wildtype. This study concluded that the status of the brain ECS is altered in AD. Modifications to the performance of the ECS were made in the form of chronic administration of a CB1 receptor antagonist (SR141716A1rimonabant) and a CB2 receptor agonist (JWH133). Chronic administration of SR141716A was able to reverse some learning impairments in APPswe/PS18E9 animals. In contrast, chronic administration of JWH133 resulted in impaired memory extinction in both wildtype and APPswe/PS18E9 mice. The results support the potential benefit of modulating the endocannabinoid system in the treatment of memory impairment in AD.